Novel Current Feedforward Average Current Mode Control technique to improve output dynamic performance of DC-DC converters - Chrin, P.; Bunlaksananusorn, C. (My University, 2007)
This paper proposes a novel Current Feedforward Average Current Mode Control (CFACMC) technique to improve output dynamic performance of DC-DC converters. In this new control scheme, besides its usual role as a feedback variable to a current controller, the sensed inductor current is fed forward, through a low-pass filter circuit, to sum with an output signal from a voltage controller to form the control signal. In the paper, the operating principle of CFACMC and its small signal model are described. From the small-signal model, the expression for selecting the gain of the low-pass filter to yield the improved output voltage response is derived. Both simulated and experimental results are provided to show that significant improvement in output dynamic response is achieved with CFACMC. © 2007 IEEE.
Keywords: Average current mode control; DC-DC converters